Innovative diagnostics and treatment : nanorobotics and stem cells - Jadczyk, Tomasz (SpringerBriefs in applied sciences and technology. Nanotheranostics., 2017)
This book focuses on nanorobotic agents and stem cells for biomedical applications. It is intended for researchers and clinicians interested in innovative diagnostic and therapeutic strategies based on nanorobots and stem cells. It presents current advances in the field of molecular machines, which could be applied to generate novel therapeutic-diagnostic systems.